Marek's Disease Virus Disables the ATR-Chk1 Pathway by Activating STAT3 - Lian, Xue (J Virol, 2019)
Oncogenic virus replication often leads to genomic instability, causing DNA damage and inducing the DNA damage response (DDR) pathway. The DDR pathway is a cellular pathway that senses DNA damage and regulates the cell cycle to maintain genomic stability. Therefore, the DDR pathway is critical for the viral lifecycle and tumorigenesis. Marek’s disease virus (MDV), an alphaherpesvirus that causes lymphoma in chickens, has been shown to induce DNA damage in infected cells. However, the interaction between MDV and the host DDR is unclear. In this study, we observed that MDV infection causes DNA strand breakage in chicken fibroblast (CEF) cells along with an increase in the DNA damage markers p53 and p21. Interestingly, we showed that phosphorylation of STAT3 was increased during MDV infection, concomitantly with a decrease of Chk1 phosphorylation. In addition, we found that MDV infection was enhanced by VE-821, an ATR-specific inhibitor, but attenuated by hydroxyurea, an ATR activator. Moreover, inhibition of STAT3 phosphorylation by Stattic eliminates the ability of MDV to inhibit Chk1 phosphorylation. Finally, we showed that MDV replication was decreased by Stattic treatment. Taken together, these results suggest that MDV disables the ATR-Chk1 pathway through STAT3 activation to benefit its replication. IMPORTANCE MDV is used as a biomedical model to study virus-induced lymphoma due to the similar genomic structures and physiological characteristics of MDV and human herpesviruses. Upon infection, MDV induces DNA damage, which may activate the DDR pathway. The DDR pathway has a dual impact on viruses because it manipulates repair and recombination factors to facilitate viral replication and also initiates antiviral action by regulating other signaling pathways. Many DNA viruses evolve to manipulate the DDR pathway to promote virus replication. In this study, we identified a mechanism used by MDV to inhibit ATR-Chk1 pathways. ATR is a cellular kinase that responds to broken single-stranded DNA, which has been less studied in MDV infection. Our results suggest that MDV infection activates STAT3 to disable the ATR-Chk1 pathway, which is conducive to viral replication. This finding provides new insight into the role of STAT3 in interrupting the ATR-Chk1 pathway during MDV replication.